Short-term effects of sulphate and chloride on the concrete containing coal bottom ash as supplementary cementitious material - Mangi, Sajjad Ali; Mohd Haziman, Wan Ibrahim; Norwati, Jamaluddin; Mohd Fadzil, Arshad; Putra Jaya, Ramadhansyah (Elsevier Ltd, 2018)
Suphate and chloride attacks on concrete are the prominent issues in the field of durable concrete structures. Therefore, this study focused on the influence of ground coal bottom ash on the strength performances of concrete exposed to sulphate and chloride environment. In this study the ordinary portland cement was replaced with 10% of coal bottom ash by weight of cement and same water to binder ratio of 0.5 was used in all concrete mixes. The original CBA was initially ground for 2 h in Los Angeles machine. Subsequently, after passing from 300micron sieve it was further ground for the period of 20 h in a ball mill grinder, to get the similar particles sizes as to ordinary portland cement. After de-moulding samples were immersed in a water for the curing period of 28 days. Afterward, specimens were shifted in 5% sodium sulphate (Na2SO4) and 5% sodium chloride (NaCl) solutions for additional curing periods of 28, 56, and 90 days. The short-term effects of sulphate and chloride on the concrete were evaluated in terms of change in weight, variation in compressive strength and degree of damage. It was observed that the addition of CBA in concrete, gives the significant development in compressive strength, around 11.32% and 13.92% higher strength than that of the control mix in water and 5% Na2SO4 solution respectively at the exposure period of 90 days. However, the development of compressive strength in 5% NaCl solution was slower, around 6.87% decrease was observed in concrete containing CBA at the exposure period of 90 days as compared to the control mix. This study suggests that 10% of CBA as a supplementary cementitious material in concrete could reduce the negative effects of sulfate and chloride salts. The outcome of this study indicated that application of ground CBA as supplementary cementitious material in concrete increases the resistance against aggressive environment.